Interfaces among e-banking service qualities, e-customer satisfaction, and e-loyalty - Sathiyavany, N.; Shivany, S. (International Academy of Science, Engineering and Technology, 2018)
Banking is a demand-driven industry due to different preferences such as providing financial services to customers. Internet should be taken into account as an important issue for banks to delivery financial services. The internet is the ideal medium for carrying out banking activities due to its cost savings potential and speed of information transmission. From a technological and cost-driven standpoint, it may seem quite logical for banks to shift as many banking activities online as possible. At the same time, the question of how to foster customer loyalty arises when the relationship between the bank and the user becomes a virtual one. As it is completely necessary to perform a research studying the quality of services dimension in e-banking and measuring its effects on the customers’ satisfaction and loyalty, and also lack of examinations previously in this area despite the importance and steady growth of e-banking services in Sri Lanka, negligible research attention has been given to the interactions among e-banking service quality dimension,ecustomer satisfaction, e-loyalty,& personal factors in the Northern Province of SriLanka by using survey data and conceptual model. Quantitative methodology was conducted and Questionnaires were distributed to the internet banking users using Random Sampling procedure. A survey of 305 e-banking users of 7 selected banks in Northern Province of SriLanka has been conducted and a Structural Equation Modeling (SEM) approach by employing Smart PLS3 of statistical data analysis technique has been used to gain what are the interactions among e-service qualities, e-customer satisfaction, and e-loyalty and customer’s personal factors can be ensured. Based on the result of analysis it can be concluded that there is a positive interaction among e-service qualities, e-customer satisfaction, and e-loyalty and also additionally there is a moderating effect by personal factors such as age, education and personal experience & knowledge are impacted the above interactions. According to the model content, e-convenience are considered more importance by revealing that customer relies on acquiring the exact service offered (time, accuracy, customization and convenience) and how the bank is handling customer problems. Also, customers depend on e-responses which mean providing the proper assistance and attaining customer needs & remedial actions. Finally, e-trust as security measures concerns over the adoption and online banking transaction is considered important when fighting against the hackers and vulnerabilities in dealing with online banking.
Keywords: E-Banking Service; E-Service Quality; E-Customer Satisfaction; E-Loyalty